APLIKASI TEKNOLOGI FORMULASI PAKAN IKAN LELE DI KELURAHAN KASTELA - Rovina Andriani; Fatma Muchdar; Nursanti Abdullah; Ismi Musdalifah Darsan; M. Irfan; Juharni Juharni; Suryani Suryani; Gamal M Samadan; Ikbal Marus; Firdaut Ismail; Syahnul Sardi Titaheluw (Jurnal Abdi Insani, 2023)
Vocational School 4 Ternate City is one of the Vocational Schools in Kastela Village which has several expertise program concentrations, one of which is Fisheries Agribusiness. The aim of this community service is to provide knowledge and skills to students of SMKN 4 Ternate in making catfish feed as a provision for entrepreneurship in the school environment and after completing school if they are unable to continue higher education. The method used is discussion or lecture as well as understanding the theory of catfish cultivation and catfish feed management, introduction to feed raw materials and tools used as well as the practice of making catfish feed according to the formulation. Participants consisted of students and teachers at SMKN 4 Ternate City as well as students from the Aquaculture study program. Before carrying out community service activities, the fish feed that is made must be based on formulation calculations, for this reason participants are first given an understanding of feed formulation and other theories before carrying out the practice of making feed so that their understanding of feed formulation technology can be used as a reference for making fish feed. independently. The training activity on the Application of Catfish Feed Formulation Technology which was attended by students of SMKN 4 Ternate, teachers and students of the aquaculture study program can be understood easily. Raw materials are available throughout the year and are relatively easy and cheap to obtain. After this training activity is carried out, it is hoped that there will be continuity for other field activities so that it is hoped that students at SMKN 4 Ternate can continue to be involved in practicum activities and student research so that the knowledge and skills gained during the practicum can be applied at school for entrepreneurial activities for vocational school students and for entrepreneurship after graduating.